DNA methylation profiling reveals novel pathway implicated in cardiovascular diseases of diabetes - Hu, Shengqing; Chen, Lulu; Zeng, Tianshu; Wang, Wenyi; Yan, Yan; Qiu, Kangli; Xie, Yajuan; Liao, Yunfei (Frontiers in Endocrinology, 2023)
Epigenetics was reported to mediate the effects of environmental risk factors on disease pathogenesis. To unleash the role of DNA methylation modification in the pathological process of cardiovascular diseases in diabetes, we screened differentially methylated genes by methylated DNA immunoprecipitation chip (MeDIP-chip) among the enrolled participants. In addition, methylation-specific PCR (MSP) was utilized to validate the DNA microarray findings. Several aberrantly methylated genes have been explored, including phospholipase C beta 1 (PLCB1), cam kinase I delta (CAMK1D), and dopamine receptor D5 (DRD5), which participated in the calcium signaling pathway. Meanwhile, vascular endothelial growth factor B (VEGFB), placental growth factor (PLGF), fatty acid transport protein 3 (FATP3), coagulation factor II, thrombin receptor (F2R), and fatty acid transport protein 4 (FATP4) which participated in vascular endothelial growth factor receptor (VEGFR) signaling pathway were also found. After MSP and gene expression validation in peripheral blood of participants, PLCB1, PLGF, FATP4, and VEGFB were corroborated. This study revealed that the hypomethylation of VEGFB, PLGF, PLCB1, and FATP4 might be the potential biomarkers. Besides, VEGFR signaling pathway regulated by DNA methylation might play a role in the cardiovascular diseases’ pathogenesis of diabetes.